The enchanted bond that unites games to the act of thinking - Neves, Maria Apparecida Campos Mamede (Seven Editora, 2024)
The objective of this article is to discuss the importance of games in the construction of essential skills and competencies for the reflexive cognitive development of children and adolescents, especially among those who live in the poor segment (favelas), do not have the necessary physical/social support for their development. It is based on authors such as Damasio, Piaget, Huizinga, Pain and on his 20 years of experience working with groups from needy communities in Rio de Janeiro (Brazil) and several other states of the country (always supported by the National Research Center [CNPq]). It proposes a way of using the game in a playful way in the classrooms that considers not only playing, but, mainly, reflecting on the moves made and their effects. It also makes an incursion into ancestral games and the importance of their structure and their playing, often found in current games, of which one is not aware, as well as their symbolic value has been lost by most in today's times, leaving only winning for the sake of winning, profiting, winning. DOI:https://doi.org/10.56238/sevened2024.026-066